The privatization of conservation in Chile: rethinking environmental governance - Rivera, Claudio; Vallejos-Romero, Arturo (Bosque (Valdivia), 2017)
In the last decade, more than 1,500,000 ha have been declared as projects of environmental conservation in Chile, one tenth of the surface that the State has accumulated in protected territories for conservation in almost one century. The novelty is that these are private initiatives by environmental philanthropists and NGOs that have bought vast extensions of land in the Chilean south austral macroregion. This phenomenon opens a series of questions for environmental studies, because it tensions the state institutions dedicated to conservation and reconfigures environmental governance. The article examines three private conservation projects in the south of Chile and analyzes the implications that these have provoked on the traditional forms of governance in which the State has had an exclusive role. The results of the research show the emergency of new environmental governance in which new actors intervene in different scales. In this new scenario, the Non-Governmental Organizations play a decisive role. The work is an exploratory study from social sciences that attempts to contribute to environmental governance studies by examining the role of non-State actors in the definition of sectorial policies and indices of conservation.